2016
DOI: 10.1111/1365-2745.12616
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect effects of native range expansion on soil microbial community structure and function

Abstract: Summary1. Analogous to the spread of non-native species, shifts in native species' ranges resulting from climate and land use change are also creating new combinations of species in many ecosystems. These native range shifts may be facilitated by similar mechanisms that provide advantages for non-native species and may also have comparable impacts on the ecosystems they invade. 2. Soil biota, in particular bacteria and fungi, are important regulators of plant community composition and below-ground ecosystem fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 103 publications
(127 reference statements)
2
48
2
Order By: Relevance
“…Many field studies on plant invasions and soil communities have shown that exotic plant species have distinct soil communities compared to native plants growing in adjacent areas (Kourtev et al 2002a, Kourtev et al 2002b, Scharfy et al 2009, Collins et al 2016, Stefanowicz et al 2016, Gibbons et al 2017. Consistent with these results, in our experiment we also observe that the composition of the rhizosphere bacterial community differed by plant origin in all four plant pairs when plants were grown in their own field soils ( Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Many field studies on plant invasions and soil communities have shown that exotic plant species have distinct soil communities compared to native plants growing in adjacent areas (Kourtev et al 2002a, Kourtev et al 2002b, Scharfy et al 2009, Collins et al 2016, Stefanowicz et al 2016, Gibbons et al 2017. Consistent with these results, in our experiment we also observe that the composition of the rhizosphere bacterial community differed by plant origin in all four plant pairs when plants were grown in their own field soils ( Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Copiotrophic phyla adapted for rapid growth and higher potential for labile carbon metabolism in high nutrient conditions are Betaproteobacteria, Bacteroidetes, Firmicutes, and Actinobacteria. Oligotrophic phyla adapted for slow growth and higher potential for carbon storage are Acidobacteria and Verrucomicrobia (Fierer et al 2007, Collins et al 2016. Other phyla cannot be categorized into either group.…”
Section: Resultsmentioning
confidence: 99%
“…For example, nitrogen fertilization causes a consistent decrease in soil bacterial diversity and microbial biomass carbon, independent of nitrogen application rates or crop types (Dai et al 2018). Nitrogen fertilization is also related to increased relative abundances of Proteobacteria and Actinobacteria (Ramirez et al 2010, Zhou et al 2017, Dai et al 2018, which include taxa that are adapted to high nitrogen demand and labile carbon pool metabolism (Fierer et al 2007, Collins et al 2016. Conversely, in North American remnant prairies, where plant organic material inputs control the growth of these copiotrophic taxa, Verrucomicrobia, which are thought to specialize in recalcitrant carbon degradation, are more predominant members of the community (Fierer et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with Grime's (, ) concept that community biomass is inversely proportional to plant stress, intermediate elevations had the highest plant cover and biomass (Figure , Table ), and therefore the lowest net impact of abiotic and resource stress. However, high elevations also have higher soil moisture, soil organic C and N, as well as microbial biomass and activity than lower elevations (Collins, Carey, Aronson, Kopp, & Diez, ), suggesting higher resource stress at low elevations. Further, while Callaway et al.…”
Section: Discussionmentioning
confidence: 99%